Semiotics Analysis of Roland Barthes' Theory on Pocari Sweat's "Sweat For Dream" Advertisement. - Wijayanto, Catur sunu; Iswari, Fitria (Cultural Syndrome, 2021)
Semiotics originates from the Greek word semeion which means "sign". According to language, a branch of science that studies the relationship of sign forms such as code, language, signals, and others. Ferdinand de Saussure introduced semiotics using the form of a sign: signified and a signifier which is atomistic. The relationship is an association between "marked" and "marked". Then, Barthes, a follower of Ferdinand de Saussure, who holds the view that a sign system that reflects the assumptions of the wider community at a certain time. According to Roland Barthes' semiology, denotation is a form of significance in the first stage, whereas connotation is the second stage. In this case denotation is more associated with closed meaning. It is like a reaction to reject the oppressive form of denotation necessity. Barthes tries to refuse, because according to him there are only connotations (Budiman, 1999: 22). Advertising is often associated with denotation and connotation through the media of promotion. Structurally, advertisements have signs, a combination of audio and visuals, have a product description and even an implied message in the ad serving. Advertising aims to promote an item or product. The advertisement that will be used as the object of study and will be analyzed is an advertisement about one of the famous body fluid replacement drink products, namely Pocari Sweat. To achieve this level of analysis, this study uses the theory of semiotics from Roland Barthes' thought. This study used a qualitative method, namely descriptive research on the semiotic analysis of Roland Berthes' thoughts in the Pocari Sweat "Sweat for Dream" ad.